INHIBITION OF MANGKOKAN LEAF (Nothopanax scutellarium Merr.) ETHANOL EXTRACT ON THE GROWTH OF Salmonella typhimurium BACTERIA - Sari, Herninda Dhama; Octavia, Bernadetta (Indonesian Journal of Bioscience (IJOBI), 2024)
Typhoid fever is an infectious disease of the digestive tract caused by the bacterium Salmonella typhimurium. Mangkukan leaf (Nothopanax scutellarin Merr.) can be an alternative treatment because it contains flavonoids, saponins, tannins, and alkaloids. This study aimed to determine the ability of Mangkukan leaf extract as an antibacterial in inhibiting the growth of S. Typhimurium bacteria. This study used a factorial completely randomized design consisting of two factors, namely the concentration of the extract and the age of the inoculum with 4 repetitions. The concentration of the extract used was 5%, 10%, 20%, 40%, and 80%, equipped with the positive control (chloramphenicol), and negative control (aqua dest), while the age of the inoculum was based on the growth phase of the test bacteria, namely 3 hours, 6 hours, 18 hours. hours, and 24 hours. Antibacterial activity testing was carried out using the Disc Diffusion method (Kirby-Bauer Test). The test concentrations of 5%, 10%, 20%, 40%, and 80% test concentrations resulted in inhibition zone diameters of 3.41 mm, 5.4 mm, 6.04 mm, 7.43 mm, and 9.48 mm, respectively. The 80% concentration of ethanol extract from the kukukan leaf was effective in inhibiting the growth of S. typhimurium bacteria with an antibacterial effectiveness value of 60.81%.